دراسة وثائقية في أبرز الصفات الجسدية لليهود في مصر خلال العصرين البطلمي والروماني - سعدالدين، إيناس أحمد عبدالغني (جامعة الأزهر - كلية الدراسات الإنسانية, 2021)
اعتاد اليهود المجيء إلى مصرفي فترات متقطعة من تاريخهم القديم حيث أصبحت مصر بلدا يألفون الحياة فيها وأقاموا فيها منذ عصور سحيقة. فقد عاشوا في مصر بين المصريين وامتزجوا معهم وكلنا يعرف أن الأصول اليهودية ربما ترجع لسيدنا إبراهيم عليه السلام أي إلى القرن الثامن عشر ق.م ثم ارتحلوا وانتشروا إلى العديد من البلدان والتي من بينها فلسطين حيث ولد إسحاق عليه السلام ومن إسحاق يعقوب. وتستهدف هذه الدراسة دراسة الصفات الجسدية لليهود المقيمين في مصر، ومدى التقارب والاختلاف فيما بينهم وبين سكان البلاد الأصليين من المصريين، وليس المجال هنا تتبع أصول اليهود منذ القدم حتى أواخر العصر الروماني، فقد تناول هذا العديد من الأبحاث التي ركزت في المقام الأول على اليهود وأصلهم ووجودهم في مصر وأحوالهم السياسية، والاجتماعية، والعسكرية، والاقتصادية. بينما تركز هذه الدراسة على صفاتهم الجسدية فقط ومحاولة الفهم هل كان اليهود يؤلفون نمطا جسديا منفردا مختلف عن باقي السكان أم أن الصفات التشريحية الملازمة لهم صفات متقاربة مع صفات المصريين وغيرهم من السكان. وأنهم لا يؤلفون وحدة جسدية خاصة بهم. لذا تعتبر هذه الدراسة تتبع لأبرز الصفات الجسدية الواضحة لديهم مقارنة بغيرهم من خلال الوثائق البردية حيث قدمت الوثائق إجابة شافية لتساؤلات عديدة حول هذا الموضوع. خاصة أنه تعذر علينا الحصول على تماثيل خاصة باليهود في تلك الفترة. لذا فإنه من دواعي الأمل لاستكمال الدراسة أن الوثائق البردية قد سدت هذا العجز الأثري حيث تناولت بالفعل العديد من الوثائق الكثير من الصفات الجسدية الملصقة باليهود. سواء الوراثية منها أو المكتسبة من صفات الوجه والقامة ولون البشرة وغيرها من الصفات التشريحية المختلفة. وقد اتبعت المنهج التحليلي الاستنباطي في الدراسة التي تدور في عدة محاور رئيسية ألا وهي الصفات المكتسبة والموروثة وتتناول الصفات المكتسبة أبرز الصفات وهي الختان وبعض الصفات الأخرى التي نجدها مشتركة مع الصفات الوراثية وتنقسم الصفات الوراثية أو الموروثة إلى لون البشرة، شكل الرأس، ملامح الوجه، صفات القامة، بالإضافة إلى صفات أخرى توضحها الدراسة."
The Jews used to come to Egypt in intermittent periods of their ancient history, as Egypt became a country where they are familiar with life and have resided there since ancient times. They lived in Egypt among the Egyptians and mixed with them, and we all know that the Jewish origins may go back to our master Abraham, peace be upon him, that is, to the eighteenth century BC. Then they migrated and spread to many countries, including Palestine, where Isaac, peace be upon him, was born and from Isaac Jacob. This study aims to study the physical characteristics of the Jews residing in Egypt, and the extent of the affinity and difference between them and the indigenous Egyptian population of the country. The scope here is not to trace the origins of the Jews from ancient times until the late Roman era, This dealt with many researches that focused primarily on the Jews, their origin and presence in Egypt, and their political, social, military, and economic conditions. While this study focuses on their physical characteristics only, and trying to understand whether the Jews had a single physical pattern different from the rest of the population, or whether the anatomical characteristics inherent in them were similar to those of the Egyptians and other populations. And they do not compose a physical unit of their own. Therefore, this study is a follow-up to the most prominent physical characteristics that are evident to them compared to others through the papyrus documents, where the documents provided a satisfactory answer to many questions on this subject. Especially since it was not possible for us to obtain statues of Jews in that period. Therefore, it is hoped to complete the study that the papyrus documents have filled this archaeological deficit, as many documents have already dealt with many of the physical characteristics attached to the Jews. Whether hereditary or acquired from facial characteristics, stature, skin color and other various anatomical characteristics. I have followed the method Analytical deductive in the study, which revolves around several main axes, namely, acquired and inherited traits. stature, in addition to other characteristics explained by the study.
Keywords: اليهود -- الصفات الجسدية -- مصر -- العصر البطلمي -- العصر الروماني